2012
DOI: 10.5539/ijbm.v7n10p142
|View full text |Cite
|
Sign up to set email alerts
|

Key Performance Indicators (KPIs) and Shipping Companies Performance Evaluation: The Case of Greek Tanker Shipping Companies

Abstract: If you are not sure where you are, how will you find out where to go?The aim of this paper is to examine the applicability and usefulness of performance indicators in shipping management performance and evaluation.The paper brings the importance of KPIs closer to the reader and examines their definition, purpose and role in the shipping market. The first part is devoted to literature review on KPIs. The second part is the methodology, where a questionnaire is taken across the tanker shipping companies in Greec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…cost, quality and time [39]. Quality, delivery, customer services, time measures, utilization of resources, costs and flexibility can be used to build a framework to measure performance of companies, and companies' executives need to choose the number of KPIs that are linked to the business strategy [40]. Even some studies claim that the cost, time and quality are more noticeable criteria to evaluate company's performance, other studies reveal that the successful companies are using more complex key performance indicators.…”
Section: Determination Of Evaluation Criteriamentioning
confidence: 99%
“…cost, quality and time [39]. Quality, delivery, customer services, time measures, utilization of resources, costs and flexibility can be used to build a framework to measure performance of companies, and companies' executives need to choose the number of KPIs that are linked to the business strategy [40]. Even some studies claim that the cost, time and quality are more noticeable criteria to evaluate company's performance, other studies reveal that the successful companies are using more complex key performance indicators.…”
Section: Determination Of Evaluation Criteriamentioning
confidence: 99%
“…In a limited number of studies, models for multi-criteria decision-making are used. The research shown in [37] has indicated that KPIs are necessary to improve internal organization, relationship with customers, competitiveness, and strategy planning in the case of tanker companies in Greece. Nathnail et al [38] used the analytic hierarchy process (AHP) to assess the significance of each criterion in KPIs and the overall performance of two terminals.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This created a gap as to why not a carrier selection research be done from freight forwarder's perspective as well. Literature also supported that container shipping lines have different customers; however, the core customers are freight forwarders (Konsta and Plomaritou, 2012). Freight forwarders have huge volumes and carriers are mostly working with freight forwarders to get more business.…”
Section: Introductionmentioning
confidence: 99%